2011
DOI: 10.1093/pcp/pcr060
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Genome-Wide Analysis of the Xylogen-Type Gene Family

Abstract: In higher plants, many extracellular proteins are involved in developmental processes, including cell-cell signaling and cell wall construction. Xylogen is an extracellular arabinogalactan protein (AGP) isolated from Zinnia elegans xylogenic culture medium, which promotes xylem cell differentiation. Xylogen has a unique structure, containing a non-specific lipid transfer protein (nsLTP) domain and AGP domains. We searched for xylogen-type genes in the genomes of land plants, including Arabidopsis thaliana, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
1
44
0
1
Order By: Relevance
“…Two zinnia xylogen orthologs were found in Arabidopsis (AtXYP1 and AtXYP2), with in addition 11 xylogen-like genes, of which two (AtXYLP7 and AtXYLP10) were expressed in stems [84]. Moreover, several rice xylogen ortholog genes were highly expressed in vascular tissues [85].…”
Section: Arabinogalactan Proteins Putatively Involved In Secondary Wamentioning
confidence: 99%
“…Two zinnia xylogen orthologs were found in Arabidopsis (AtXYP1 and AtXYP2), with in addition 11 xylogen-like genes, of which two (AtXYLP7 and AtXYLP10) were expressed in stems [84]. Moreover, several rice xylogen ortholog genes were highly expressed in vascular tissues [85].…”
Section: Arabinogalactan Proteins Putatively Involved In Secondary Wamentioning
confidence: 99%
“…The contribution of other factors such as ATP binding cassette (ABC) transporters and Rac small guanosine-5′-triphosphatase ( GTPase) to intercellular messaging is also established (Supplemental File S5). The involvement of various players in the intercellular signalling clearly shows that the life and death in zinnia cell cultures and the differentiation of xylem cells in planta is under strict control (Ogawa et al 1997; Barceló 1998a, b; Groover et al 1997; Endo et al 2001; Hosokawa et al 2001; Motose et al 2001a, b, 2004; Yamamoto et al 2001, 2007; Dahiya et al 2005, 2006; Karlsson et al 2005; Pesquet et al 2005, 2013; Tokunaga et al 2005; Ito et al 2006; Fukuda et al 2007; Avci et al 2008; Hirakawa et al 2010; Kobayashi et al 2011; Kondo et al 2011; Novo-Uzal et al 2013; Schuetz et al 2013; Farquharson 2014; Escamez and Tuominen 2014; Bollhöner et al 2012, 2013; Wang et al 2013; Ménard and Pesquet 2015; Sauter 2015; Serk et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Double mutants for Arabidopsis homologs, AtXYP1 and AtXYP2, show defects in xylem formation. Sequence analysis in silico indicated that there are 13 XYP-like genes in Arabidopsis [144]. Because they showed diversity in the tissue expression pattern, xylogen-type arabinogalactan proteins may mediate cell-cell communication in different biological events.…”
Section: Xylogenmentioning
confidence: 99%